Russia's New Authoritarianism Putin and the Politics of Order - Lewis, David G. (Edinburgh University Press, 2020)
Studies the transformation of Russian domestic politics and foreign policy under Vladimir PutinAsks what kind of political system 'Putinism' denotesEngages with the scholarly and policy debate on the growth of illiberal politics and authoritarianism globally in the post-Soviet space and in countries as diverse as Hungary, Egypt, Turkey and the PhilippinesUses contemporary case studies - including Russia's legal system, the annexation of Crimea and Russian policy in Syria - to critically examine Russia's political ideologyWhy did Russia's post-Soviet political system developed into a new form of authoritarianism? And how did its foreign policy came to pose such a profound challenge to the West? David G. Lewis goes beyond current polemical debates to address these questions.Lewis investigates the Russian understanding of key concepts such as sovereignty, democracy and political community. He analyses the Russian political system as a novel form of authoritarian political order, unpacking the ideological paradigm that underpins it. He reveals that Russia's new order is characterised by the consolidation of political and economic power around a sovereign leader, together with a willingness to take political decisions outside the law both at home and in international affairs.